Zasób dokumentów drukowanych polskich bibliotek naukowych i ich wykorzystanie w latach 1991-94 - Górny, Mirosław; Jazdon, Artur (My University, 1997)
The paper contains results of the questionnaire study targeted at estimation of printed materials resources and their use in Polish research libraries. The results are split with respect to the library type (academic/special) and specialization (chemistry, life sciences, technical sciences etc.). The data presented include overall volume of monographs and serials collections and the volume of yearly acquisitions. The percentage of foreign materials with English literature singled I out is also given. Additional information in this section includes data about acquisitions on the order of library users and acquisition processing time. The second group of the data includes circulation statistics, the number of unsatisfied requests, estimations of collections use, interlibrary loans statistics and collection pruning policies. In addition, there is an information about studies of users needs, easy access policies (e.g. Saturday and Sunday opening hours and loans on weekend days).
PRINTED DOCUMENTS RESOURCES IN POLISH RESEARCH LIBRARIES AND THEIR USE IN 1991-1994